Identifikasi Ektoparasit pada Benih Ikan Mas (Cyprinus carpio) di Balai Benih Ikan Kabat, Kabupaten Banyuwangi - Mohammad Faizal Ulkhaq; Darmawan Setia Budi; Gunanti Mahasri; Kismiyati - (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Diseases caused by parasitic groups get less serious attention from the farmers because it is chronic morbidity and mortality rates and small. However, if observed further, parasitic diseases may trigger secondary infection by bacteria, viruses and fungi that can cause death and high losses. Thus this study aims to identify the types of ectoparasites that infected the seed goldfish in BBI Kabat, Banyuwangi which the results will be used as an early warning to prevent the death of fish in bulk. The research sample in the form of seeds 3-5 cm carp amounted 150 obtained from BBI Kabat, Banyuwangi. Ectoparasites inspection method performed by scraping the surface of the body, fins and gills of fish, and then observed under a microscope with a magnification ranging from 40-400x. The observation of ectoparasites are further identified accordance morphology based on the keys of identification. Identified ectoparasites infect seed goldfish in BBI Kabat, Banyuwangi consists of 8 genus is Zoothamnium sp., Trichodina sp., Oodinium sp., Vorticella sp., Argulus sp., Lernaea sp., Dactylogyrus sp., and Gyrodactylus sp. Further research is needed to determine the prevalence and intensity of parasites and appropriate measures to prevent the spread of parasites in healthy fish in BBI Kabat, Banyuwangi.